Foreign aid in a world in crisis : shifting geopolitics in the neoliberal era - Jakupec, Viktor, 1945-; Kelly, Max, 1979-; McKay, John (Professor) (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"This book investigates the geo-politicization of foreign aid in recent years, against a background of global overarching crises such as climate change, conflict, COVID-19, economic crisis, energy shortages and migration. Foreign aid has historically been understood as assisting both with the development objectives of the recipients, and with the trade and geopolitical interests of the donors. In the first decades of the 21st Century, however, this balance has been shifted by a series of complex global challenges. The book argues that donors have now moved towards framing aid as a geopolitical instrument, wherein aid can be given or withheld based on power or political intent, thus imposing the donor's specific values and norms. The book provides an in-depth analysis of this weaponization of foreign aid within a framework of global disruption and ultimately concludes that the world is at a tipping point towards a new socio-political world order. Asking important questions about the power dynamics at play within the aid sector, this book will be an important read for researchers across development studies, political science, international relations, and global affairs"--
Foreign aid and world order(s), a political economy of crisis and disruptors -- A critique of the neo-liberal world order : a foreign aid perspective -- Crises and disruptors of world order(s) : the first decades of the 21st century -- A critique of contemporary foreign aid -- The geo-politicization of aid -- Geopolitical crises and the changing role of aid.
Keywords: Economic assistance; Geopolitics; BUSINESS & ECONOMICS / Development / Economic Development; POLITICAL SCIENCE / International Relations / General; POLITICAL SCIENCE / Globalization